Prevalence of Corruption within the Administration Police Service in Kenya: A Case of Kirinyaga County - Okwomi, Augustine O.; Karari , Peter; Njoka K, Johannes (African Journal of Education,Science and Technology (AJEST), 2020)
The menace of corruption continues to ravage societies and world economies, and Kenya in particular. There have been concerns regarding the vice of corruption within the police service especially the Administration Police (AP). The vice is believed to negatively influence service delivery to the citizens. The purpose of this study was to analyze the prevalence of corruption within the AP service in Kirinyaga County in Kenya. The study adopted the descriptive research design. The target population was 500 AP officers from five sub counties in Kirinyaga County and Kathuri and Pals sampling formula was used to select a sample of 50 police officers. From every sub-county, 10 police officers were selected using the stratified random sampling technique for the study, making a total of 50 officers. The Sub County Administration Police Commander and the County Administration Police Commander, DAPC/CONCAP hereafter referred to as police commanders were purposively sampled. Data was collected using questionnaires for police officers and interview schedules for police commanders. Collected data was analyzed using both the descriptive and inferential statistics with the aid of Statistical Package for Social Sciences (SPSS) version 20. The results of the study indicated existence of widespread corruption where 36 (77%) of the respondents said that there was favouritism or nepotism in the stations when dealing with deployment or promotions of AP officers against 11 (23%) of those who had opposing views. Bribery of senior officers by their juniors was reported as a common occurrence within the AP service where senior officers asked for bribes in order to treat their junior colleagues in a favourable manner. Specifically, cases of favouritism reported involved promotions, house allocations, duty assignments and transfers. Junior officers paid the bribes in cash or in kind such as through sexual exchanges especially for female officers (43%). Regarding corruption risky areas, junior officers were particularly mistreated by their seniors (43%), who directly or indirectly asked for bribes. The study concluded that corruption in the Administration police was basically initiated by the senior police officers who demanded bribes from their juniors and public in return for services. From the study findings, it is recommended that there is need to address the menace of corruption among the Administration Police by examining the relationship between the senior and junior police officers in terms of promotions, allocation of assignments and transfers. Open channels of communication should be developed where the officers could freely express their concerns under protection from reprisals from their seniors.